Decline management: the case of cash. Policy response in the Netherlands and the Nordic countries - Bram Scholten (Deutsche Bundesbank, 2017)
The Netherlands and the Nordic countries are faced with a rapid decline in the use of cash. Sooner or later, they will be confronted with the question whether cash remains necessary as well-functioning means of payment for POS transactions. This paper focuses on how this issue is addressed in the Netherlands and the Nordics, based on answers to a detailed questionnaire submitted to the central banks of these countries, covering the three main elements of the well-functioning of cash: paying in cash, drawing cash from, and lodging cash in one's bank account. All central banks seem to believe that at least for the foreseeable future, cash remains needed as well-functioning means of payment. Leaving legal issues aside, main arguments are that for part of the population, use of electronic payment instruments is not, or not always, possible or desirable. In addition, cash functions as fall back in case of temporary breakdowns in the functioning of, or trust in, the electronic payment system. In Norway and the Netherlands, this view seems shared by the government and society at large. As far as Denmark, Finland and Sweden are concerned, a broad consensus and a general policy to `manage' the decline of cash have not or not yet materialized. Once authorities and society at large are convinced that cash remains needed as well-functioning means of payment, it has to be determined whether, and if so which, specific action is required to keep cash well-functioning as means of payment. In this respect, unlike the market approach (at least so far) favored in Sweden, Norway and the Netherlands adopted a pro-active approach, with the idea that it is easier to prevent unwelcome developments than to correct them once they have occurred. In the Netherlands, agreement has been reached on a cooperative approach.
Keywords: 330; cash; cashless society; legal tender